Penerapan Rule of Reason Dalam Putusan Komisi Pengawas Persaingan Usaha Pada Kasus Penguasaan Pasar - Hariz, Naufal (Jurnal Suara Hukum, 2023)
Competition is a necessity in the business world, business actors are no stranger to competition between business actors in conducting their business activities. This competition can have a positive impact on the business world itself. However, not all business actors respond positively to this competition, in practice there will be many business actors who choose fraudulent or bad methods to gain profits, such as engaging in monopolistic practices that can cause or create an unfair business competition climate. This paper will discuss the application of the rule of reason approach in regulating market control based on Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition by also examining their application in KPPU decision Number: 22 / KPPU-I / 2016.